2018
DOI: 10.1111/bcpt.12963
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticle‐induced Cytokine Responses in BEAS‐2B and HBEC3‐KT Cells: Significance of Particle Size and Signalling Pathways in Different Lung Cell Cultures

Abstract: We have previously reported that silica nanoparticles (SiNPs) of nominal size 50 nm (Si50) induce the pro-inflammatory cytokines CXCL8 and IL-6 in BEAS-2B cells, via mechanisms involving MAPK p38, TACE-mediated TGF-α release and the NF-κB pathway. In this study, we examined whether these findings are cell specific or might be extended to another epithelial lung cell model, HBEC3-KT, and also to SiNPs of a smaller size (nominal size of 10 nm; Si10). The TEM average size of Si10 and Si50 was 10.9 and 34.7 nm, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…IL-1β release is due to silica particle-induced activation of the inflammasome due to uptake of particles causing destabilization of the lysosomal membrane [12,16,18,63,64]. Furthermore, we have in previous studies found that SiNPs also are able to induce gene expression and release of IL-1α and IL-1β in lung epithelial cells at rather low concentrations [11]. Interestingly, IL-1α and IL-1β are both known to be critical paracrine (and endocrine) mediators of inflammation linked to lung [34,60,65,66] and cardiovascular disease [35,36].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…IL-1β release is due to silica particle-induced activation of the inflammasome due to uptake of particles causing destabilization of the lysosomal membrane [12,16,18,63,64]. Furthermore, we have in previous studies found that SiNPs also are able to induce gene expression and release of IL-1α and IL-1β in lung epithelial cells at rather low concentrations [11]. Interestingly, IL-1α and IL-1β are both known to be critical paracrine (and endocrine) mediators of inflammation linked to lung [34,60,65,66] and cardiovascular disease [35,36].…”
Section: Discussionmentioning
confidence: 87%
“…Both types of particles induce cytotoxic, genotoxic and pro-inflammatory acute responses [1,4,8]. In previous studies we have investigated SiNP-induced cytotoxicity, cytokine gene expression and release as well as underlying signalling pathways involved, in lung epithelial cells and macrophages in mono-cultures [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrosilicate NTs and chrysotile were dissolved in PBS with 0.15% BSA to final concentration of 2 mg/mL, and sonicated on ice for 20 minutes to a final energy of 7056 J. The silica NP solution sized 10 nm (Si10) was diluted in PBS with 0.15% BSA after a sonication step . Characterization of Si10 was done in a previous study …”
Section: Methodsmentioning
confidence: 99%
“…The cells were exposed as described in our previous study. 23 THP-1 monocytes were maintained in RPMI-1640 with 10% FBS at a cell density of 0.5 mill/ml and differentiated to macrophage-like cells (THP-1 macrophages) by exposing to PMA. THP-1 cells were seeded three days before exposure on a 35-mm 6-well plate at a cell density of 0.5 mill/mL or 1 × 10 5 cells on a 96-microwell culture plate in RPMI-1640 with 10% FBS.…”
Section: Cell Culture and Exposure Conditionsmentioning
confidence: 99%
See 1 more Smart Citation